The meroplankton community of the oceanic Ross Sea during late summer. Issue 4 (16th December 2013) - Gallego, R.; Lavery, S.; Sewell, M.A.
Abstract Meroplankton community studies in the Antarctic have primarily focused on the coastal waters of both the Antarctic Peninsula and the Ross Sea. The New Zealand International Polar Year - Census of Antarctic Marine Life (IPY-CAML) voyage to the Ross Sea during the late summer (February–March) 2008 provided the first meroplankton samples from three regions in the deep, oceanic waters of the Ross Sea (shelf, slope and adjacent offshore Antarctic waters of Admiralty Seamount and Scott Island). We used a combined morphological and molecular approach to identify 36 larval operational taxonomic units based on sequences from three loci (16S, 18S, COI), and exclude early developmental stages of holoplankton. Overall, larval abundance was lower than previous Antarctic studies (5.19 specimens per 100 m3), with larvae most abundant in the first 200 m of the water column and most diverse in the shelf region. Multivariate analysis revealed significant differences in the meroplankton community between regions and depth ranges, but with low similarity within these groupings; differences between water masses were undetectable due to the confounding effect with both region and depth. The influence of nearby benthic populations (e.g. the acorn barnacle Bathylasma corolliforme) and/or locally abundant taxa (e.g. the nudibranch Tergipes antarcticus) was evident in the meroplankton community.